Implementasi Program Kampung Keluarga Berencana (Kb) Di Desa Sribunga Kecamatan Buay Pemuka Bangsa Raja Kabupaten Ogan Komering Ulu Timur (OKUT) - Elsa Lettiyani; Isabella Isabella; Novia Kencana (UNIVERSITAS INDO GLOBAL MANDIRI, 2020)
The family planning village program is a new innovation packaged by the government to strengthen the family planning and family development population program by narrowing the scope of targets, namely the village level area unit and certain criteria. The research raised the problem of how the village family planning program was implemented in Sribunga village, Buay Pemuka Bangsa Raja sub-district, Ogan Komering Ulu Timur district and how the village family planning program was implemented in improving community welfare. The purpose and usefulness of the writer of this thesis is to know the implementation of the KB village program in Sribunga Village, Buay Pemuka Bangsa Raja Subdistrict, East OKU Regency. In this thesis the author uses qualitative research methods ranging from data collection methods used are observation, interviews and documentation, descriptive with the stages of data reduction, data exposure, and conclusions. The results showed that by using the theory of Edward III to analyze there are four indicators, namely (1) communication seen from the delivery of information, clarity of information and socialization has gone well, it's just that the clarity of information has not gone well as expected because the target group has not been that way. be able to understand what the implementor said. (2) Resources there are three sub indicators, namely human resources, budget resources and facility resources. The implementation of the village family planning program in Sribunga village is not sufficient because human and budgetary resources have not been able to support the success of the village family planning program. (3) The disposition in implementing the attitude of the implementors and target groups is quite good in responding to the KB village program, it's just that the knowledge and understanding of the implementers in Sribunga Village is not yet optimal, which makes program implementation activities not yet having an impact on improving welfare. (4) The structure of the bureaucracy in implementing the SOP is guided by the technical manual for the KB village and fragmentation is structured.Keywords: Implementation, village family planning program, welfare